Human chemerin correlation in gingival crevicular fluid and tear fluid as markers of inflammation in chronic periodontitis and type‐2 diabetes mellitus. Issue 1 (29th July 2015) - Patnaik, Kaushik; Pradeep, A. R.; Nagpal, Kanika; Karvekar, Shruti; Singh, Priyanka; Raju, Arjun
Abstract: Aim: The aim of the present study was to evaluate the levels and correlation of human chemerin in gingival crevicular fluid (GCF) and tear fluid in chronic periodontitis (CP) subjects with and without type‐2 diabetes mellitus (DM). Materials and methods: A total of 40 subjects were divided into three groups: group 1 had 10 periodontally healthy subjects; group 2 consisted of 15 CP subjects and group 3 had 15 type‐2 DM subjects with CP. The GCF and tear fluid levels of human chemerin were quantified using enzyme linked immunosorbent assay (ELISA). Systemic parameters such as body mass index, glycated hemoglobin levels and fasting plasma glucose levels were evaluated. The clinical outcomes evaluated were gingival index (GI), probing depth (PD), and clinical attachment level (CAL), and the correlations of the two inflammatory mediators with clinical parameters were evaluated. Results: Human chemerin levels increased from group 1 to group 2 to group 3. The GCF and tear‐fluid values of the inflammatory mediators correlated positively with each other and with the evaluated periodontal parameters ( P < 0.05). Conclusion: Human chemerin can be considered as possible GCF and tear‐fluid markers of inflammatory activity in CP and DM.